Preferences for Multipurpose Technology and Non-oral Methods of Antiretroviral Therapy Among Women Living With HIV in Western Kenya: A Survey Study - Bernard, Caitlin; Jakait, Beatrice; Fadel, William F.; Mocello, A. Rain; Onono, Maricianah A.; Bukusi, Elizabeth A.; Wools-Kaloustian, Kara K.; Cohen, Craig R.; Patel, Rena C. (Frontiers in Global Women's Health, 2022)
Introduction Understanding interests in and preferences for multipurpose technology (MPT) for the co-administration of contraception and antiretroviral therapy (ART) and alternative, non-oral ART methods among women living with HIV (WLHIV) is vital to successful implementation of future treatment options, such as long-acting injectable ART. Methods Between May 2016 and March 2017 we conducted a cross-sectional telephone survey of 1,132 WLHIV of reproductive potential with prior experience using intermediate- or long-acting contraceptive methods in western Kenya. We present descriptive statistics and multinomial logistic regression to evaluate predictors of interest in specific MPT and non-oral ART methods. Results Two-thirds (67%) reported interest in MPT, with the most common reason for interest being ease of using a single medication for both purposes of HIV treatment and pregnancy prevention (26%). Main reasons for lack of interest in MPT were need to stop/not use contraception while continuing ART (21%) and risk of side effects (16%). Important characteristics of MPT were effectiveness for pregnancy prevention (26%) and HIV treatment (24%) and less than daily dosing (19%). Important characteristics of non-oral ART methods were less than daily dosing (47%), saving time accessing ART (16%), and effectiveness of HIV treatment (15%). The leading preferred methods for both MPT and non-oral ART were injectables (50 and 54%) and implants (32 and 31%). Prior use of a contraceptive implant or injectable predicted interest in similar methods for both MPT and non-oral ART methods, while this relationship did not appear to vary between younger vs. older WLHIV. Discussion Most WLHIV in western Kenya are interested in MPT for HIV treatment and contraception. Prior exposure to contraceptive implants or injectables appears to predict interest in similar methods of MPT and non-oral ART. Developers of MPT and non-oral ART methods should strongly consider WLHIV's preferences, including their changing reproductive desires.